2010
DOI: 10.1007/s10725-010-9515-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term exposure to copper on the lichen photobiont Trebouxia erici and the free-living algae Scenedesmus quadricauda

Abstract: In the present work, the long-term effect (14 days) of copper on the levels of intracellular and total copper accumulation, growth, assimilation pigment composition, chlorophyll a fluorescence, soluble protein content and oxidative status (production of hydrogen peroxide and superoxide) in two algal species (Scenedesmus quadricauda and Trebouxia erici) was assessed. Scenedesmus quadricauda is a free-living alga while Trebouxia erici is the photobiont of a lichen. The presence of copper negatively affected grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In the accordance with the results of this study, decreases of F V /F M ratios due to Cu excess in short-term experiments using the lichen C. arbuscula subsp. mitis as well as due to chronic Cu excess in axenic cultures of lichen photobiont Asterochloris erici (Piovár et al, 2011) were previously observed. However, the presence or absence of UA in the lichen thalli had no significant effect on the degree of chlorophyll a fluorescence in thalli of C. arbuscula subsp.…”
Section: Discussionmentioning
confidence: 73%
“…In the accordance with the results of this study, decreases of F V /F M ratios due to Cu excess in short-term experiments using the lichen C. arbuscula subsp. mitis as well as due to chronic Cu excess in axenic cultures of lichen photobiont Asterochloris erici (Piovár et al, 2011) were previously observed. However, the presence or absence of UA in the lichen thalli had no significant effect on the degree of chlorophyll a fluorescence in thalli of C. arbuscula subsp.…”
Section: Discussionmentioning
confidence: 73%
“…Decrease of the growth can be relatively easily determined and reflects physiological status of the algal cells (Juraj et al 2011). Heavy metals had adverse effects on the growth of Scenedesmus quadricauda (Mohammed and Markert 2006; Stork et al 2013) and Spirogyra setiformis (Çelekli et al 2016) in cultures, same result also was found in this study, the inhibited of growth is mainly under high cadmium concentration, the growth of C. vulgaris decreased with the increasing cadmium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of malondialdehyde (MDA) increased with the increase in copper concentration in the nutrient solution (Monnet et al, 2005). The presence of copper negatively affected the oxidative status of the lichen photobiont (Piovár et al, 2011).…”
Section: Introductionmentioning
confidence: 99%